SURFACE ROUGHNESS AT PLASMA CUTTING (Nonconventional Technologies Review, 2017)
Distinct cutting methods could be applied to separate parts from a plate workpiece. Nowadays, among such methods, the thermal plasma allows obtaining a relatively narrow slot, a high cutting speed and a cut surface appreciated as acceptable in certain situations. Essentially, the thermal plasma is generated by sending a gas through the electric discharge developed between the central electrode and the nozzle, as components of the plasma generator. The analysis of plasma cutting process showed that there are some groups of actors able to affect the heights of asperities generated by the cutting process on the cut surface. A full factorial experiment with three independent variables at two levels was designed and achieved by considering some of process input factors whose values could be easier modified, to investigate their influence on the value of the Ra surface roughness parameter. By processing the experimental results, a power type function was determined. The analysis of this empirical mathematical model and of the elaborated graphical representations highlighted the influence exerted by the cutting speed, plate workpiece thickness and current intensity on the Ra surface roughness parameter.
Keywords: plasma cutting; surface roughness; influence factors; experimental research; empirical mathematical model; cutting speed; workpiece thickness; current intensity